Scripting Intelligence: Web 3.0 Information Gathering and Processing - Watson, Mark (Apress, 2013)
This book covers Web 3.0 technologies from a software developer’s point of view. While nontechies can use web services and portals that other people create, developers have the ability to be creators and consumers at the same time—by integrating their work with other people’s efforts.